KONSEP MANUSIA MENURUT MOHANDAS KARAMCHAND GANDHI - Ngurah Weda Sahadewa (Jurnal Filsafat "WISDOM", 2013)
The background of this work is to explore the nature of man. So it can be discovered an explanation, especially according to Gandhi’s thought. The material object of this work is Gandhi’s thought and its formal object is the philosophy of man. Gandhi’s thought has an interest in a lot of things about social, politics, economic, cultural, moral and religion. In this point of view is showed about human problem which is a relationship with non-violence, God and truth. The work’s method is historical-factual method. The steps are to decide of work’s theme, to collect, to categorize, and to interpret of data. The result of this work is that Gandhi’s thought builds a relationship between the human with non-violent, God and truth. Love is based on Ahimsa (non-violence). Non violence is stress one thing that the fullness to ignore non-violence. This becomes a basic to find the truth. In other side, finding the nature of truth can help finding the nature of God.